Chemical composition of volatile component from citrus species / Nurul Hakimah Ismail - Ismail, Nurul Hakimah (Faculty of Applied Sciences, 2016)
This study was carried out to determine the chemical composition of the volatile component from the kaffir lime (Citrus hystrix), calamondin (Citrus microcarpa), pomelo (Citrus maxima). These three sample leaves were extracted with hexane by using hydrodistillation method. All the volatile oils were identifying by using GC-MS and comparison by previous work. The major component for volatile oil from the leaf Citrus hystrix were Hexatoporphyrin (62.9%), oxime (82.3%), linalool (80.2%), terpine 4-01 (60.0%), and a- tripenol (55.6%). On the other hand, oxime (88.2%), (1s, 2R, 5R)-2-(-hydroxypropan-2-yl)-5-methyl chyclohexanol (20.4%) and p- methane-3, 8-diol, cis-I, 3, trans-I, 4 (69.4%) were found to be major chemical constituent in Citrus microcarpa. Finally, identification on the volatile oil of Citrus have afforded oxime (86.5%) (9), Terpinen-4-01 (64.8%),2,6- octadienal (56.6%), and (1R, 4Ar 7r, 8aR)-7-(2- hydropropan-2-yl)-1 (80.5 %), respectively.